Evolutionary relationships of West Nile virus detected in mosquitoes from a migratory bird zone of Colombian Caribbean (2015)
ABSTRACT: Background: West Nile virus (WNV) is a member of the genus Flavivirus, and it is transmitted between Culex sp. mosquitoes and avian hosts. Equids and humans are commonly infected with WNV as dead-end hosts, and the signs and symptoms of infection range from mild illness to neurologic symptoms as encephalitis, meningitis and sometimes death. Previous phylogenetic studies have classified WNV into six genetically distinct lineages and provided valuable insight on WNV dispersal patterns within the Americas and its emergence in different geographic areas. In this study, we isolated, sequenced and genetically characterized the NS5 and envelope genes for two WNV strains detected from Northern of Colombia. Herein we describe the evolutionary relationships with representative WNV-strains isolated in a variety of epidemic outbreaks and countries, to define the phylogeographic origin and possible implications in the epidemiology of this emergent virus in Colombia. Findings: Fragments of the NS5 and Envelope genes were amplified with RT-PCR and sequenced to obtain 1186-nt and 1504-nt portions, respectively. Our sequences were aligned with 46 sequences from WNV-strains collected in the U.S., Mexico and Argentina for phylogenetic reconstruction using Bayesian methods. Sequence analyses identified unique non-synonymous substitutions in the envelope gene of the WNV strains we detected, and our sequences clustered together with those from the attenuated Texas – 2002 genotype. Conclusions: A new strain closely related to attenuated strains collected in Texas during 2002 was identified from Colombia by phylogenetic analysis. This finding may explain the absence of human/equine cases of WNV-encephalitis or severe disease in Colombia and possibly other regions of South America. Follow-up studies are needed in ecosystems used by migratory birds areas and virological/entomological surveillance.